SATIRICAL POLITENESS CONSTRUCTION IN “WAR MACHINE” MOVIE - M. Syaifuddin S. (JEELL (Journal of English Education, Linguistics and Literature) English Departement of STKIP PGRI Jombang, 2022)
Not many studies considered politeness in movie as politeness that was deliberately constructed by the director for a specific purpose. This research views that in part of War Machine movie scenes contained some constructions of politeness, politeness involving satire as a means of criticism, which we called Satirical Politeness.  Scenes containing actions or satiric utterances, whether delivered by speakers (S) or hearer (H) in managing their faces, were the focus of this study. Qualitative analysis of movies produced as a reaction after the attacks of 19/11/01 was called 'qualitative under fire' (Denzin, 2009a). Data were analyzed using Brown & Levinson's (1987) perspectives. They were measured by looking for Weightiness. The Weightiness was determined by how strong the ranking of imposition was. The rank of imposition (Rx) was determined by the high and low of P (position) between the speech participants, and it was determined by the far and near distance (D) of the speech participants.  There were many meanings behind the facework that each actor played concerning satire. The satirical politeness in the War Machine movie applied in several ways, namely; 1) satirical attitude to show disagreement, 2) jumping politeness strategy to save the face of the interlocutor, but still attacking his face in a more relaxed way, 3) anecdotal bald on record attitude used to reduce the credibility of real characters outside the movie, 4) Creating negative stigma of a real character by attaching hedge and exaggerate acts, 5) praising with insulting meanings through Bald on record and  exaggerate.